Biomarker composition and origin of Miocene pale lignites in China and Serbia - Bangjun LIU; Jingzhi LI; Ksenija STOJANOVIĆ; Jiazhong HUANG; Yueting LIU; Yumeng SUN; Dragana ŽIVOTIĆ; Jinxi WANG; Yuzhuang SUN; Cunliang ZHAO (Meitan xuebao, 2025)
Pale lignites are widely distributed in Cenozoic lignite basins around the world, but their origin is still controversial. Identifying their organic matter composition and formation mechanism is of great significance for reconstructing paleoclimate changes and clean and low-carbon utilization of lignite resources. Taking the Miocene pale lignite from Kolubara Basin in Serbia and Mile Basin in Yunnan, China as the research objects, organic geochemical methods, such as Soxhlet extraction, column chromatography separation and gas chromatography-mass spectrometry, were used to qualitatively and quantitatively analyze biomarker compounds in aliphatic and aromatic hydrocarbons to explore the differences in vegetation composition, microbial degradation and sedimentary environment during the coalification process of light and dark lignites. The results show that the pale lignite in Mile Basin has a high content of long-chain n-alkanes (up to 82.5%), showing a significant contribution from leaf waxes of terrestrial higher plants (mainly angiosperms), accompanied by a lower aquatic plant indicator value (Paq of 0.16) and a higher plant leaf wax index (Pwax of 0.86), indicating that its coal-forming environment was relatively dry and accompanied by strong microbial degradation; while the dark lignite has an increased proportion of medium-chain and short-chain n-alkanes, indicating that the input of aquatic plants and lower organisms was enhanced during the sedimentation process in Mile Basin. Both the pale and dark lignite in Kolubara are mainly contributed by gymnosperms. Content of diterpenoids in their aliphatic hydrocarbons is extremely high (87.3% for pale and 82.5% for dark), and the relative mass fraction ratio of diterpenoids to diterpenoids + triterpenoids is close to 1, reflecting the predominance of conifers in the peatland. At the same time, the higher relative mass fraction ratio of C31(R)hopane to total hopane and C30 hop-17(21)-ene to C30αβhopane reveal that Kolubara lignites were formed under relatively oxidative, acidic and low thermal evolution conditions. In addition, perylene and higher CWDI values indicate that pale lignite in two basins was subjected to stronger degradation, which is consistent with the higher content of hopane. By comparing the differences between Cenozoic pale and dark lignite, it is clarified that the sedimentary environment is the main controlling color change of lignite.